ANALISIS PELAKSANAAN ASAS LUBERJURDIL PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN REPUBLIK INDONESIA PERIODE 2019-2024 PADA MAHASISWA UNIVERSITAS RIAU - Khoirul Romodhan; Supentri Supentri; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated because in this modern era the world experiences quite strong shocks of values and norms. The moral and ethical crisis of national life, especially the crisis of values in the political aspect, is so pronounced. The deviation of private ethics and public ethics in the state has experienced an increase and chaos of norms as if it continues to occur in state management practices so that in an atmosphere of globalization we are hesitant to face it, with a responsive attitude. This study aims to find out an analysis of the implementation of the Luberjurdil principle of the presidential and vice presidential elections of the republic. Indonesia for the period 2019-2024. In managing the data, the researcher used quantitative descriptive analysis. The sample of this study were 100 people. The data collection used by researchers is to use questionnaires, interviews, observations, documentation. Based on the recapitulation results of the calculation of respondents who answered YES with an average of 91.47 with a percentage of 91.47%, while those who answered NO were with an average of 8.53 with a percentage of 8.53%. So it can be concluded that the analysis of the implementation of the Luberjurdil principle for the presidential and vice presidential elections of the Republic of Indonesia for the 2019-2024 period for university students in Riau, proved that they answered YES with a percentage of 91.47% in the answer range of 51% -100%, then it can be said "Good". Key Words: Luberjurdil lection Principle